1987
DOI: 10.1177/074823378700300203
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Induction Studies On Seven Phthalate Esters

Abstract: Seven phthalate esters, representing a variety of chain lengths and degrees of branching in the alcohol moiety, were tested for their ability to produce peroxisome proliferation in the Fischer 344 rat. Di(2-ethylhexyl)adipate (DEHA) was tested using the same protocol and di(2-ethylhexyl)phthalate (DEHP) was run with each study as an internal control. Each ester was administered in the feed for a period of 21 days at levels of 2.5%, 1.2% and either 0.6% or 0.3%. DEHP and DEHA were also fed at levels of 0.1% and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
0
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(25 citation statements)
references
References 10 publications
4
19
0
2
Order By: Relevance
“…In the rat, liver weight and liver hypertrophy were clearly increased by DEHP, CINN and DCB, as reported by others (30)(31)(32). MON, ETU, and LIM also gave weak increases in liver weight that were sometimes accompanied by liver hypertrophy.…”
Section: Ratsupporting
confidence: 58%
See 2 more Smart Citations
“…In the rat, liver weight and liver hypertrophy were clearly increased by DEHP, CINN and DCB, as reported by others (30)(31)(32). MON, ETU, and LIM also gave weak increases in liver weight that were sometimes accompanied by liver hypertrophy.…”
Section: Ratsupporting
confidence: 58%
“…All of the compounds tested gave increases in cytochrome P450, determined either as total (spectral) P450 or as specific isoforms (Western blots). Where the P450 induction profiles of compounds have previously been described (32,35,36), the results were as expected; for example, the peroxisome proliferator DEHP gave clear increases in total P450 and CYP 4A1 and some weak increases in CYP 2B1/2. In some cases, CEA, for example, total P450 was not increased, but there was weak induction of CYP 2B1/2 and CYP 3A1.…”
Section: Ratmentioning
confidence: 49%
See 1 more Smart Citation
“…By far, this hallmark feature associated with administration of PPARα ligands in rats and mice is the best and well-accepted phenotype that serves as a biomarker that determines the classification of chemical compounds into the class of peroxisome proliferators. A number of investigators over past 30 years demonstrated that DEHP exhibits similar effects on peroxisomal oxidases and other enzymes, as well as density and number of peroxisomes in hepatocytes, in both rats and mice [23,24,80,32]. Multiple strains of rats and mice and both sexes in these species are responsive, and both time-and dose-response have been reported.…”
Section: Proliferation Of Peroxisomes and Induction Of Peroxisomal Prmentioning
confidence: 99%
“…1 Peroxisome proliferators (PPs) constitute a diverse group of rodent nongenotoxic hepatocarcinogens, including the hypolipidemic drug nafenopin, 2,3 and chemicals of industrial and environmental importance such as the phthalate plasticizers. 4 In rats and mice, PPs cause hepatic peroxisome proliferation and perturb hepatocyte growth regulation leading to liver enlargement and, ultimately, to tumors. 5,6 In vivo, PPs cause peroxisome proliferation, oxidative stress, and the induction of the enzymes of ␤-oxidation.…”
mentioning
confidence: 99%